Gastrodiplomacy Jepang di Indonesia Melalui Program Japan Halal Food Project (JHFP) Tahun 2013-2015 ( - Rizal Adam, Muhammad Fuad; Iqbal, Muhammad; Trihartono, Agus (e-Sospol, 2017)
Abstract Gastrodiplomacy denotes a form of public diplomacy which aggregates the diplomacy germane to culture, food, and establishing national achievement (nation branding) so as to make foreign culture omnipresent and come true. The objective of gastrodiplomacy is to elevate positive image of a country through the utilization of food. Food, which is a part of culture in every country, is deemed a sound bridge of nonverbal communication to bring various parties together, and, when seriously dealt with, it will make massive contribution to economic growth of a country. The utilization of food constitutes a part of the whole creative economy development by combining omnifarious elements from the concept of culture diplomacy, building national reputation (nation branding) and halal principle in order to elevate positive image of a country. This particular strategy was opted by Japan in Indonesia through implementing Japan Halal Food Project from 2013 to 2015. This study grappled with discovering and describing the processes and ways implemented by Japan government in Indonesia, which used food as the focal instrument in creating an image of Muslim-friendly country. The research method applied was descriptive qualitative, which aimed at elaborating the process and ideas on the creation of Japan’s image as a Muslim-friendly country through Japan Halal Food Project in Indonesia from 2013 to 2015. Research data were collected by library study and interview. The research findings indicated that Japan gastrodiplomacy through Japan Halal Food was carried out by combining public diplomacy, culture diplomacy, nation branding, and Halal certification. The very program was made operative through a number of information disseminations by website, cooking tutorial, seminar, and business matching, the objectives of which were to create an image of Japan being a Muslim-friendly country .